Mycotoxins in Feed Grains and Ingredients - Herrman, Tim J.; Trigo-Stockli, Dionisia; Pedersen, John (My University, 1995)
This publication discusses the cause, clinical signs, government regulations, reconditioning/ detoxification strategies, and detection technology associated with mycotoxins in grain.
MF2061_1995_10
Keywords: MF2061; Crops; Equipment and structures; livestock; MF